Implementation of Nitrate Directive to Poland - Mariusz FOTYMA; Irena DUER (Acta Agriculturae Slovenica, 2006)
In the paper the present state of implementation of three main resolutions of Nitrate Directive is presented. Polish Code of GAP has been prepared already in 1999 in collaboration with Danish Advisory Service in Agriculture and after approval by Ministry of Agriculture and Rural Development and Ministry of Environment, disseminated in several thousands copies. The 21 vulnerable zones have been established in 2004 by Regional Water Management Boards covering 6263 km2 i.e. 2 % of Polish territory. Action programmes have been prepared for each vulnerable zone separately and the implementation of these programmes is in progress. The case study for one vulnerable zone was included.